In Vitro Anti-Staphylococcus aureus Activity of Nigella sativa L. Seed Oil Extract, Compared with CXM, CEC, MAN and CAZ Antibiotics (Institue of Medicinal Plants, ACECR, 2006)
Background: The anti-microbial effect of plants has been suggested from old years. New researches in this field confirm such property of applications. Objective: In this study, anti-microbial effects of Nigella sativa seed oil cold extract against two strains of Staphylococcus aureus was evaluated, and the Minimum Inhibitory Concentration (MIC) of Nigella sativa L. (NS) was compared with relevant antibiotics. Methods: Detection of MIC in NS oil cold extract was performed using broth dilution method. The original extract was prepared in 0.5%, 0.25%, 0.06% and 0.03% concentrations by serial dilution. S. aureus strains (ATCC 1112 and 2572) were grown in TSB media to 0.5 MC Farland standard concentrations and each 0.01 dilution of microorganism suspension above was transferred to the drug dilution. Tubes were incubated overnight at 35 C. The sensitivity of the bacteria were defined by Disk Diffusion (kirby-bauer) Method and Antibiogram disks made by Difco Inc . The obtained values were compared with the effects of the extract. Results: MIC for S. aureus ATCC-2572 and S. aureus ATCC-1112 were found 1/16 and 1/10, respectively. It was revealed by performing in vitro sensitivity tests for the two strains that NS oil can affect the bacterial pure form in 0.125% and 0.26% concentrations. Conclusion: It is suggested that the anti-microbial effect of NS oil extract is comparable with antibiotics such as CXM, CEC, MAN, CAZ. We recommend experimental use of Nigella sativa L. to control some of bacterial infections.